2020
DOI: 10.1111/head.13914
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Psychiatric Comorbidities on Headache‐Related Disability in Migraine: Results From the Chronic Migraine Epidemiology and Outcomes (CaMEO) Study

Abstract: Objective To examine the influences of depression and anxiety on headache‐related disability in people with episodic migraine or chronic migraine. Background Depression and anxiety are common comorbidities in people with migraine, especially among those with chronic migraine. Methods This cross‐sectional analysis of data from the longitudinal, internet‐based Chronic Migraine Epidemiology and Outcomes Study assessed sociodemographic and headache features, and headache‐related disability (Migraine Disability Ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
68
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 62 publications
(72 citation statements)
references
References 45 publications
4
68
0
Order By: Relevance
“…Differences were also significant between the CM group and the HFEM group, though the magnitude of the difference was much larger for the HFEM vs L/MFEM groups. As MHDs increase, it has been previously demonstrated that MIDAS scores increase 33,34 . It is, therefore, plausible that differences in disability are a consequence of increased MHDs.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Differences were also significant between the CM group and the HFEM group, though the magnitude of the difference was much larger for the HFEM vs L/MFEM groups. As MHDs increase, it has been previously demonstrated that MIDAS scores increase 33,34 . It is, therefore, plausible that differences in disability are a consequence of increased MHDs.…”
Section: Discussionmentioning
confidence: 97%
“…As MHDs increase, it has been previously demonstrated that MIDAS scores increase. 33,34 It is, therefore, plausible that differences in disability are a consequence of increased MHDs. There were no significant differences in headache impact as measured by the proportion requiring bed rest during a typical migraine attack between the pairs of groups we contrasted.…”
Section: Discussionmentioning
confidence: 99%
“…5 Impacts on family and social life, difficulty making plans or commitments, and emotional/affective and cognitive distress are also common among migraine patients. [6][7][8] naïve group and 12.4 days (SD = 7.0) for treatment experienced patients. The majority had severe Migraine Disability Assessment (Grade IV, total score ≥21), including 67.1% Conclusions: Prior to 2018, the burden of migraine was high for patients initiating preventive treatments.…”
Section: Introductionmentioning
confidence: 99%
“…Migraine‐related disability impacts productivity at work, school, and functioning at home 5 . Impacts on family and social life, difficulty making plans or commitments, and emotional/affective and cognitive distress are also common among migraine patients 6–8 …”
Section: Introductionmentioning
confidence: 99%
“…Depression was among the most commonly reported comorbid conditions in a survey of patients with migraine (63.8%) 9 . Longitudinal research demonstrates that depression among migraine patients is associated with a 56% greater risk of moderate/severe migraine‐related disability 10 . Consequently, patient‐reported outcomes (PROs) are a critical component of evaluating the effects of new treatments on HRQoL, emotional and psychological well‐being, disability status, and occupational functioning 11 .…”
Section: Introductionmentioning
confidence: 99%